2003
DOI: 10.1016/s0309-1740(02)00248-6
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality in male fallow deer (Dama dama): effects of age and supplementary feeding

Abstract: Thirty-two male fallow deer, half 18- and half 30-month-old, were slaughtered after a 4-month feeding trial on pasture alone or with daily supplement of 500 g (dry matter) concentrate/head (eight each 18- and 30-month-old). Neither diet nor age produced significant effects on M. longissimus thoracis et lumborum (LM) and on M. semimembranosus (SM) pH and colour. Meat texture properties (Warner-Bratzler-WB Shear Force and compression), water loss and collagen content were unaffected by diet, while the older deer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
88
6
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 19 publications
32
88
6
1
Order By: Relevance
“…0.05) with a further increase of carcass maturity. Correspondingly, the collagen solubility showed an increase (P , 0.05) from maturities A to C, and then decreased (P , 0.05) from C to D. This is different from other studies, which indicates no or negatively age-related changes in the insoluble or soluble collagen content, or in the collagen solubility (Miller et al, 1983;Volpelli et al, 2003). The differences in collagen between the present study and others could be explained by breed and feeding regimes.…”
Section: Resultscontrasting
confidence: 96%
See 1 more Smart Citation
“…0.05) with a further increase of carcass maturity. Correspondingly, the collagen solubility showed an increase (P , 0.05) from maturities A to C, and then decreased (P , 0.05) from C to D. This is different from other studies, which indicates no or negatively age-related changes in the insoluble or soluble collagen content, or in the collagen solubility (Miller et al, 1983;Volpelli et al, 2003). The differences in collagen between the present study and others could be explained by breed and feeding regimes.…”
Section: Resultscontrasting
confidence: 96%
“…Bailey (1985) attributed the tougher texture of beef in older cattle to the mature collagen crosslinks and Bosselmann et al (1995) found a high concentration of pyridinole crosslink in tough beef. Moreover other researchers gave proofs that the shrinkage temperature of intramuscular connective tissue (IMCT) increased (Judge and Aberle, 1982) and collagen solubility decreased when meat tenderness decreased (Volpelli et al, 2003). Thus intramuscular connective tissue is an important factor to meat tenderness.…”
Section: Introductionmentioning
confidence: 99%
“…Adult springbok had lower L*, a*, and chroma values and, higher hue angle values in comparison to subadults; but no differences in b* values were observed. Conversely, Volpelli et al (2003) found no differences in color between male deer aged 18 and 30 mo.…”
Section: Animal Agementioning
confidence: 73%
“…However, beef from grazing animals also generally contains higher concentrations of antioxidants, which can protect against lipid and myoglobin oxidation (Insani et al, 2008). Wiklund et al (2006) found that the venison from grazing animals had better color stability than meat from pellet-fed animals, possibly due to higher levels of vitamin E. In contrast, other studies on venison reported no differences in meat color between concentrate and pasture diets (Volpelli et al, 2003;Hutchison et al, 2012). Although Gatellier et al (2005) have implicated color and color stability variations on differences in Mb content in animals fed different diets, Wiklund et al (2006) observed no differences in Mb content between meat from pellet-fed and grazing animals.…”
Section: Feeding Managementmentioning
confidence: 99%
“…This popularity may stem from the relatively low-input production system required to rear fallow deer and the minimal impact their husbandry has on the environment (Volpelli et al, 2003). Thus, market potential exists for the increased production of fallow deer for export and local consumption within South Africa.…”
Section: Introductionmentioning
confidence: 99%